Catalyst for preparing succinic acid through maleic acid water phase hydrogenation as well as preparation and application of catalyst

By introducing additives and surfactants into the catalyst support and increasing the hydroxyl group on the surface of the support through water vapor treatment, the problem of loss of active components of the catalyst under hot acid conditions is solved, and a catalyst with high stability and high yield is achieved, supporting Large-scale production of succinic acid.

CN119386892AActive Publication Date: 2025-02-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202310926562.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-07
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

The existing aqueous phase hydrogenation catalysts are prone to de-activated components under hot acid conditions, resulting in low catalyst stability and yield, making it difficult to achieve large-scale production.

Method used

Using titanium dioxide containing additives as a support, the number of hydroxyl groups on the surface of the carrier is increased by water vapor treatment, which promotes the high dispersion and stable adhesion of active metal components, and optimizes the hydrogenation activity of the catalyst and Selective.

Benefits of technology

The stability and hydrogenation activity of the catalyst are significantly improved, and the maleic acid conversion rate can be achieved above 99.9% and succinic acid yield can be achieved above 99.5% under mild reaction conditions, and multiple recycling applications are supported.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386892A_ABST
    Figure CN119386892A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing succinic acid through maleic acid water phase hydrogenation as well as preparation and application of the catalyst. The catalyst comprises a carrier and an active metal, the carrier is a titanium dioxide carrier containing an auxiliary agent, and the auxiliary agent is selected from at least one of La, Ga, Re, Mo, In, Ni and Mn. When the catalyst is used for preparing succinic acid through maleic acid water phase hydrogenation, the catalyst has the advantages of being high in succinic acid yield and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for preparing succinic acid by aqueous phase hydrogenation of maleic acid and its preparation and application, belonging to the technical field of catalysts. Background Art

[0002] As an important organic chemical raw material and intermediate, succinic acid is widely used in many fields such as medicine, food, and chemical industry. It is the main raw material for biodegradable plastic polybutylene succinate (PBS). It has huge potential market demand and is considered to be one of the most promising biorefining products in the future.

[0003] The main methods for preparing succinic acid include electrochemical synthesis, biological fermentation, catalytic hydrogenation, etc. Among them, catalytic hydrogenation has the advantages of high conversion rate, high product purity, high yield, no obvious side reactions, and green environmental protection, and is currently the most widely used industrial synthesis method.

[0004] The preparation of succinic acid by catalytic hydrogenation can be divided into a non-aqueous phase method and an aqueous phase method. The non-aqueous phase method is to prepare succinic acid by catalytic hydrogenation under organic solvent or solvent-free conditions. It includes directly hydrogenating maleic acid to obtain succinic acid, or using maleic anhydride as a reactant, catalytic hydrogenation to obtain succinic anhydride, and then hydrolyzing the anhydride to obtain succinic acid. CN111841551A discloses a method of using tetrahydrofuran as a solvent, maleic anhydride under the action of a catalyst, and reacting with hydrogen to generate succinic anhydride. In this process, an organic solvent is used, the solvent consumption is large, and there is a high production cost and great environmental harm. At the same time, the prepared succinic anhydride needs to be distilled to remove the solvent, and then further hydrolyzed to obtain succinic acid. The process flow is relatively complicated and will cause unnecessary product loss. However, the solvent-free method has a slow reaction rate and low selectivity of the target product, and there are few related reports of this type.

[0005] The aqueous phase method uses water as a solvent, and hydrogenates maleic anhydride or maleic acid under a certain catalytic system to prepare succinic acid. The presence of maleic acid and succinic acid in the aqueous solution causes the solution to be strongly acidic (pH < 3). Under the reaction conditions, the influence of hot acid solution on the stability of the catalyst cannot be ignored. Therefore, the preparation of acid-resistant catalysts is a research focus. CN101844976B discloses a method for preparing succinic acid by hydrogenating one or more of maleic anhydride, fumaric acid, and maleic acid, using SiO2, ZrO2, AC, TiO2 or SiC as a carrier, and the active component is selected from transition metals such as Fe, Co, Ni, Pd, Pt, Ru, and Ir. However, this method does not investigate the stability of the catalyst, and the problem that the active component is easily lost under hot acid conditions cannot be ignored. Under long-term operation conditions, the stability of the catalyst needs to be solved urgently.

[0006] At present, in order to improve the acid resistance and stability of the catalyst, the main research methods reported include carbon layer coating on the surface of the catalyst. Among them, CN106861702A discloses a method for preparing a Cu-Ni / Al2O3@C catalyst for direct synthesis of succinic acid by aqueous hydrogenation of maleic anhydride. Among them, maleic anhydride is first hydrolyzed to obtain maleic acid, and then hydrogenated to obtain succinic acid. However, the main component of the catalyst carrier is the amphoteric compound Al2O3. In this acidic reaction system, the carrier properties are prone to change. At the same time, the carbon layer coating further increases the diffusion resistance and reduces the reaction rate. CN103191767B adopts the same idea and prepares an acid-resistant catalyst with γ-Al2O3 as a carrier and N-doped carbon material coating. Similarly, the γ-Al2O3 carrier is prone to property changes under reaction conditions. At the same time, the uneven coating of the carbon layer is also prone to the loss of the carrier γ-alumina and the deactivation of the catalyst.

[0007] On the other hand, the preparation ideas of acid-resistant catalysts also include the use of inert carriers. CN111330580B and CN111330581A disclose catalysts and their applications for preparing succinic acid by aqueous phase hydrogenation of maleic acid. Using activated carbon, α-alumina, silicon dioxide or silicon carbide as carriers, the force between the inert carrier and the active component is enhanced by pretreatment of the carrier surface or addition of additives, thereby reducing the loss of active components and improving the stability of the catalyst. However, even after pretreatment and addition of additives, the binding force between the active component and the inert carrier is still weak. Under long-term operation conditions, the loss of active components is still prominent. At the same time, activated carbon materials have rich pore structures. Under the same loading conditions, active components are easily attached to the inside of the pores, and the contact between the reactants and the active components may be restricted by the pores, resulting in low catalytic activity. In addition, the catalyst preparation process is relatively complicated and difficult to prepare on a large scale. CN102430404A uses activated carbon or silicon dioxide as a carrier to prepare an acid-resistant catalyst for hydrogenating Ru-loaded maleic acid to synthesize succinic acid, and there is also a problem of weak binding force between the inert carrier and the active component. CN112979455A discloses a method for preparing succinic acid by hydrolyzing maleic anhydride and then hydrogenating it, using carbon materials as carriers, including carbon microspheres, activated carbon, and water-resistant honeycomb activated carbon, and there are also problems of poor binding between the inert carrier and the active component and large diffusion resistance. CN107473954A discloses a green production method for preparing succinic acid by hydrogenating at least one of maleic anhydride, maleic acid, and fumaric acid, using CMK-3 mesoporous carbon, Y-MCM-41 mesoporous molecular sieve, M41S mesoporous silica, and FDU-15 mesoporous resin as carrier materials, wherein the carbon material and the silica material have the problem of weak binding with the active component, the instability of the molecular sieve carrier in the water phase, and the low-strength nature of the resin carrier, which limits the further promotion and use of such catalysts.

[0008] In summary, the preparation of succinic acid by aqueous phase hydrogenation can avoid the use of organic solvents and reduce environmental hazards. At the same time, the product succinic acid can be separated by cooling crystallization, which is simple to operate. However, in this process, the hot acid solution is extremely corrosive under heating conditions, which easily causes the catalyst properties to change and the active component to be lost. Therefore, it is urgent to develop a highly active, acid-resistant, scalable aqueous phase hydrogenation catalyst for preparing succinic acid, so as to produce succinic acid at low cost, low energy consumption and low pollution. Summary of the invention

[0009] In view of the technical problems existing in the prior art, the present invention provides a high-activity and high-stability catalyst for preparing succinic acid by aqueous phase hydrogenation of maleic acid, and its preparation and application. When the catalyst of the present invention is used for preparing succinic acid by aqueous phase hydrogenation of maleic acid, it has the advantages of high succinic acid yield and good stability.

[0010] The first aspect of the present invention provides a catalyst for preparing succinic acid by aqueous phase hydrogenation of maleic acid, wherein the catalyst comprises a carrier and an active metal, the carrier is a titanium dioxide carrier containing an additive, and the additive is selected from at least one of La, Ga, Re, Mo, In, Ni and Mn, preferably at least one of La, Ga and Ni.

[0011] Furthermore, the carrier is a titanium dioxide carrier containing an additive, and the additive, calculated as oxide, accounts for 0.01% to 1.0% of the mass of TiO2 in the carrier, preferably 0.2% to 1.0%.

[0012] Furthermore, the number of surface hydroxyl groups per unit area of ​​the carrier is 5 to 15 (×10 mmol / m 2 ).

[0013] Furthermore, the carrier is a non-molded body (i.e., powder) with an average particle size of 6 to 30 μm. The carrier can also be made into a shaped body, and the powder can be made into a shaped body of appropriate size according to actual needs using a conventional molding method, and the average particle size of the powder before molding is 6 to 30 μm.

[0014] Furthermore, the active metal is selected from at least one of Pd, Pt, Ru, Rh and Ir, and the content of the active metal accounts for 0.1 wt% to 2.0 wt% of the mass of TiO2 in the carrier.

[0015] Furthermore, in the catalyst, the carrier crystal form is anatase type.

[0016] Furthermore, the specific surface area of ​​the catalyst is 10 to 40 m 2 / g.

[0017] The second aspect of the present invention provides a method for preparing the above catalyst, comprising:

[0018] (1) a solution A containing titanium and an additive reacts with an aqueous solution B containing a precipitant and a surfactant;

[0019] (2) filtering, washing, drying, and steam-treating the slurry obtained in step (1) to obtain a carrier;

[0020] (3) impregnating the support obtained in step (2) with a solution containing active metal components, and drying and calcining the impregnated material;

[0021] (4) reducing the material prepared in step (3) to obtain the catalyst.

[0022] Furthermore, in step (1), in the solution A containing titanium and an additive, the titanium source may be a soluble titanium salt, and the additive source may be a soluble additive metal salt. The soluble titanium salt is preferably at least one of titanium oxysulfate and titanium oxynitrate. The soluble additive metal salt may be at least one of nitrate, sulfate, and chloride.

[0023] Furthermore, in step (1), in the solution A containing titanium and additives, the concentration of Ti is 1.5 to 2.5 mol / L, and / or the amount of the additive added in terms of oxide is 0.01% to 1.0%, preferably 0.2% to 1.0%, of the mass of the titanium source in terms of TiO2.

[0024] Furthermore, in step (1), in the aqueous solution B containing a precipitant and a surfactant, the precipitant is at least one of urea and hexamethylenetetramine, and the surfactant is at least one of dodecylbenzenesulfonic acid, anionic polyacrylamide (molecular weight of 12 million to 20 million), and polyethylene glycol (molecular weight of 400 to 8000). Furthermore, in step (1), in the aqueous solution B containing a precipitant and a surfactant, the concentration of the precipitant is 2 mol / L to 4 mol / L. Furthermore, in step (1), the amount of surfactant added is 0.5 wt% to 3.0 wt% of the mass of titanium in solution A as measured by TiO2.

[0025] Furthermore, in step (1), the reaction mode of liquid A and liquid B can be forward addition or reverse addition. In step (1), the reaction temperature is 75°C to 95°C, the reaction time is 2h to 6h, and the pH value at the reaction end point is 1.0 to 3.0.

[0026] Furthermore, in step (1), the reaction mode of liquid A and liquid B can also be parallel flow. Furthermore, the reaction temperature is 75°C to 95°C, the reaction time is 2h to 6h, and the reaction pH value is 1.0 to 3.0.

[0027] Furthermore, in step (2), the filtering and washing are carried out by conventional methods. The washing is carried out by water. Furthermore, in step (2), the drying conditions are as follows: the drying temperature is 50°C to 100°C, and the drying time is 2h to 14h.

[0028] Furthermore, in step (2), the steam treatment is a continuous flow steam treatment, and the temperature is raised to the steam treatment temperature. The dry solid is in an inert gas atmosphere, and the steam treatment conditions are as follows: the steam treatment temperature is 450°C to 700°C, the treatment time is 2h to 6h, and the steam feed volume space velocity is 0.05 to 2.0h -1 .

[0029] Furthermore, in step (2), during the heating process, the inert gas is preferably N2 and / or Ar.

[0030] Furthermore, in step (2), the water vapor treatment may also contain an inert gas (such as N2 and / or Ar) when the water vapor is fed, wherein the inert gas accounts for less than 50% of the volume of the water vapor.

[0031] Furthermore, the carrier obtained in step (2) is a powder with an average particle size of 6 to 30 μm.

[0032] Furthermore, in step (3), the method of impregnating the support obtained in step (2) with the solution containing active metal components can be an equal volume impregnation method, an excess impregnation method, etc. The active metal source can be a soluble metal salt, such as at least one of chlorides, nitrates, etc.

[0033] Furthermore, in step (3), the drying conditions are as follows: the drying temperature is 80° C. to 120° C., and the drying time is 2 h to 14 h.

[0034] Furthermore, in step (3), the calcination conditions are as follows: the calcination temperature is 450°C to 700°C, and the calcination time is 2h to 4h.

[0035] Furthermore, in step (4), the reduction is carried out in a hydrogen-containing atmosphere. Preferably, the reducing gas is a mixture of hydrogen and an inert gas, wherein the hydrogen accounts for 5% to 20% of the volume of the mixed gas. The inert gas is, for example, argon or nitrogen. The reducing conditions are as follows: the reducing temperature is 500° C. to 650° C., and the reducing time is 30 min to 120 min.

[0036] The third aspect of the present invention provides an application of the above catalyst in preparing succinic acid by aqueous phase hydrogenation of maleic acid.

[0037] Furthermore, the application includes: in the presence of hydrogen, an aqueous solution of maleic acid is contacted with the catalyst to react to obtain a product.

[0038] Furthermore, the reaction can be carried out in a closed autoclave. After the reaction is completed, the solid catalyst is recovered by hot filtration, the filtrate is cooled, crystallized and dried to obtain succinic acid solid, and the remaining liquid is recycled. The hot filtration temperature is 45°C to 90°C, and the cooling crystallization temperature is 5°C to 15°C.

[0039] Furthermore, the concentration of the maleic acid aqueous solution is 5wt% to 30wt%.

[0040] Furthermore, the amount of the catalyst is 0.5wt% to 5wt% of the total mass of the maleic acid aqueous solution.

[0041] Furthermore, the reaction conditions are as follows: hydrogen pressure is 0.7MPa-4MPa, reaction temperature is 60°C-120°C, and reaction time is 1h-6h.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] (1) The catalyst of the present invention uses a titanium dioxide carrier containing an additive, and in particular, a large number of surface hydroxyl groups per unit area are favorable for the high dispersion and stable attachment of active metal components on the carrier surface, which not only inhibits the loss of active metal components but also further improves the hydrogenation activity and selectivity of the catalyst.

[0044] (2) In the preparation process of the catalyst carrier of the present invention, water vapor treatment is used to carbonize the residual organic components in the dried precursor, and the carbonized components react with water vapor to generate reducing gases H2 and CO, which are helpful for TiO2 to form oxygen vacancies. Among them, the addition of the auxiliary agent in the precursor can serve as an active component of the water gas shift reaction, promote the generation of reducing gas, thereby facilitating the formation of oxygen vacancies on the TiO2 carrier, increasing the number of hydroxyl groups on the carrier surface, and enhancing the interaction between the active metal and the carrier;

[0045] In the process of preparing the catalyst carrier of the present invention, before the steam treatment, the introduction of auxiliary agents into the TiO2-based carrier can further optimize the coordination environment of the hydrogenation active component, which is conducive to the high dispersion and stable attachment of the hydrogenation active metal component on the carrier surface. Through the above-mentioned synergistic effect, not only the loss of active metal components is suppressed, but also the hydrogenation activity and selectivity of the catalyst are further improved. In addition, an aqueous solution containing a precipitant and a surfactant is reacted with a solution containing titanium and auxiliary agents, wherein the surfactant is an important component as a dispersant and surface structure control, which can prevent the active component from agglomerating and growing. In addition, as an organic component, the surfactant can first be carbonized in the subsequent steam treatment process, and then a water-gas shift reaction can occur to form a reducing atmosphere, thereby helping to increase the number of hydroxyl groups on TiO2.

[0046] (3) The catalyst of the present invention is used for preparing succinic acid by aqueous phase hydrogenation of maleic acid, and has high hydrogenation activity and selectivity. Under mild reaction conditions, a maleic acid conversion rate of more than 99.9% and a succinic acid yield of more than 99.5% can be achieved. Moreover, the catalyst can be recycled for multiple times and still have a high succinic acid yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 is the particle size distribution diagram of the carrier in Example 1;

[0048] Figure 2 is the N2 adsorption-desorption isotherm of catalyst 1 in Example 1;

[0049] Figure 3 The XRD spectrum of catalyst 1 before and after the cyclic reaction in Example 1;

[0050] Figure 4 The XRD spectra of catalyst 5 before and after the cyclic reaction in Comparative Example 1;

[0051] Figure 5 is the particle size distribution diagram of the carrier in Comparative Example 3;

[0052] Figure 6 This is the XRD spectrum of catalyst 9 in Comparative Example 5. DETAILED DESCRIPTION

[0053] The technical scheme of the present invention is described in detail below in conjunction with the embodiments, but the present invention is not limited to these embodiments. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.

[0054] In the present invention, the steps for analyzing the number of surface hydroxyl groups per unit area of ​​the carrier are as follows: 0.3 g of the carrier is dissolved in 50 mL of a 0.1000 mol / L NaOH standard solution, stirred for 1 hour, and then acid-base titrated with a 0.1000 mol / L HNO3 standard solution, using neutral red as an indicator. When the titration endpoint is reached, the color of the solution changes from yellow to red. The number of hydroxyl groups per unit area σ can be preliminarily calculated based on the amount of acid required for the titration:

[0055] σ=(C1V1-C2V2) / Sm

[0056] Where: σ is the number of surface hydroxyl groups per unit area, mol / m 2 ; C1 is the concentration of the alkaline solution, mol / L; V1 is the volume of the alkaline solution, L; C2 is the concentration of the acid solution used for titration, mol / L; V2 is the volume of the acid solution used for titration to the endpoint, L; S is the specific surface area of ​​TiO2, m 2 / g; m is the mass of TiO2, g.

[0057] In the present invention, the particle size distribution is analyzed using a BT-9300ST laser particle size distribution analyzer (Dandong Better Instrument Co., Ltd.).

[0058] In the present invention, the N2 adsorption-desorption isotherm of the sample is tested by using the Tri StarⅡPlus specific surface analyzer of Micromeritics Company of the United States. Before the test, the sample is vacuum degassed at 150°C for 12 hours, and the specific surface area is calculated by the BET method.

[0059] In the present invention, a D8 Advance X-ray diffractometer produced by Bruker of Germany was used for XRD characterization (Cu Kα, λ=0.15406 nm, scanning range of 5-70°, step length of 0.02°).

[0060] Example 1

[0061] Catalyst 1 preparation:

[0062] (1) Add 2 mol of titanyl sulfate and 0.005 mol of La(NO)3·6H2O to 1 L of deionized water and stir to obtain liquid A; add 2 mol of urea and 1 g of dodecylbenzenesulfonic acid to 0.5 L of deionized water and stir to obtain liquid B; add 20 mL of bottom water to the reaction container, and react liquid A and liquid B in parallel with continuous stirring. The reaction temperature is 90°C, the reaction pH is 2.5, and the reaction is terminated after 2 hours.

[0063] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 h. 5 g of the dried precursor was taken and heated to 500°C under the condition of continuous N2 flow at 200 mL / min, and steam was introduced for 2 h, wherein the water vapor volume space velocity was 2 h -1 The number of surface hydroxyl groups per unit area of ​​the carrier after water vapor treatment was measured, and the results are shown in Table 1.

[0064] (3) The metal active component Pd is loaded by the over-impregnation method. First, palladium chloride is dissolved in a hydrochloric acid solution to prepare a chloropalladium acid solution (the concentration of Pd is 58 wt%). 13.80 mg of the chloropalladium acid solution is added to 20 mL of deionized water, mixed evenly, and then 4 g of the carrier prepared in step (2) is poured into the solution. After stirring at room temperature for 4 h, the filter cake is dried at 100 ° C for 8 h, and calcined at 500 ° C for 3 h to obtain a catalyst. The active component Pd loading amount is 0.2 wt% based on TiO2.

[0065] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain catalyst 1.

[0066] The particle size distribution of the carrier is shown in Figure 1 As shown, it can be seen that the particle size distribution is relatively uniform, with a particle size between 1.938 and 57.36 μm, and the average particle size is shown in Table 1. The N2 physical adsorption-desorption isotherm of catalyst 1 is shown in Figure 2 As shown in Table 1, the gas adsorption amount increases significantly when the relative pressure is greater than 0.8, indicating that it is a mesoporous material. The BET fitting results are shown in Table 1. The XRD spectrum is shown in Figure 3 As shown, it shows an anatase structure.

[0067] Catalyst 1 Evaluation:

[0068] Reaction 1: Weigh 2.5g of catalyst and add it to 100g of 30wt% maleic acid aqueous solution. After replacing the air with N2 five times, introduce hydrogen to replace N2 three times, and finally fill in 2MPa H2. Turn on the stirring to mix thoroughly, and then carry out the hydrogenation reaction at 100°C. After reacting for 4h, stop heating and the reaction is over. When the temperature of the kettle drops to room temperature, take out the mixture in the kettle, place it in an oven and heat it to 60°C. After the solution is uniform, filter it while hot to obtain the catalyst. The filtrate is placed at 5°C for cooling and crystallization. The precipitated solid is succinic acid, and the remaining liquid is re-put into the next cycle. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2. The XRD spectrum of catalyst 1 after eight cycles of reaction is shown in Figure 3 As shown, no change in crystal form was observed, indicating that the catalyst is stable.

[0069] Example 2

[0070] Catalyst 2 preparation:

[0071] (1) Add 2 mol of titanium oxynitrate and 0.015 mol of Ni(NO)2 to 1 L of deionized water and stir to obtain liquid A; add 2 mol of hexamethylenetetramine and 2 g of polyacrylamide (molecular weight 12 million) to 0.5 L of deionized water and stir to obtain liquid B; slowly add liquid B dropwise to liquid A for reaction at a reaction temperature of 90°C and a reaction end point pH of 2.0. The reaction is terminated after 6 hours of reaction.

[0072] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 h. 5 g of the dried precursor was taken and heated to 700°C under the condition of continuous N2 flow at 100 mL / min, and steam was introduced for 2 h, wherein the water vapor volume space velocity was 0.5 h -1 The number of surface hydroxyl groups per unit area of ​​the sample after water vapor treatment was measured, and the results are shown in Table 1.

[0073] (3) The metal active component Ir was loaded by the over-impregnation method. First, 57.14 mg of iridium chloride hexahydrate solution (Ir concentration 35 wt%) was added to 20 mL of deionized water, mixed evenly, and then 4 g of the carrier was poured into it. After stirring at room temperature for 4 h, the filter cake was placed at 100 ° C for 8 h and calcined at 575 ° C for 3 h to obtain the catalyst. The loading amount of the active component Ir was 0.5 wt% based on TiO2.

[0074] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 450°C for 120 minutes to obtain catalyst 2.

[0075] The particle size analysis of the carrier is shown in Table 1, and the average particle size is 24 μm. The BET fitting results of catalyst 2 are shown in Table 1, and the specific surface area is 16.84 m 2 / g.

[0076] Catalyst 2 Reviews:

[0077] Reaction 2: Weigh 2.5g of catalyst and add it to 100g of 30wt% maleic acid aqueous solution. After replacing the air with N2 five times, introduce hydrogen to replace N2 three times, and finally fill in 1MPa H2. Turn on the stirring to mix thoroughly, and then carry out hydrogenation reaction at 120℃. After reacting for 6h, stop heating and the reaction is over. When the kettle temperature drops to room temperature, take out the mixture in the kettle, place it in an oven and heat it to 60℃. After the solution is uniform, filter it while hot to obtain the catalyst, and place the filtrate at 5℃ for cooling and crystallization. The precipitated solid is succinic acid, and the remaining liquid is re-entered into the next cycle. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0078] Example 3

[0079] Catalyst 3 preparation:

[0080] (1) Add 2 mol of titanium oxynitrate and 0.008 mol of GaCl3 to 1 L of deionized water, and stir to obtain liquid A; add 2 mol of hexamethylenetetramine and 4 g of polyethylene glycol-400 to 0.5 L of deionized water, and stir to obtain liquid B; slowly add liquid B dropwise to liquid A for reaction, the reaction temperature is 95°C, the reaction end point pH is 2.0, and the reaction is terminated after 4 hours of reaction.

[0081] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 h. 5 g of the dried precursor was taken and heated to 450°C under the condition of continuous N2 flow at 400 mL / min, and steam was introduced for 6 h, wherein the water vapor volume space velocity was 1 h -1The number of surface hydroxyl groups per unit area of ​​the sample after water vapor treatment was measured, and the results are shown in Table 1.

[0082] (3) The metal active component Ir was loaded by the over-impregnation method. First, 57.14 mg of iridium chloride hexahydrate solution (Ir concentration 35 wt%) was added to 20 mL of deionized water, mixed evenly, and then 4 g of the carrier was poured into it. After stirring at room temperature for 4 h, the filter cake was placed at 100 ° C for 8 h and calcined at 575 ° C for 3 h to obtain the catalyst. The loading amount of the active component Ir was 0.5 wt% based on TiO2.

[0083] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 450°C for 120 minutes to obtain catalyst 2.

[0084] The particle size analysis of the carrier is shown in Table 1, and the average particle size is 27.3 μm. The BET fitting results of catalyst 2 are shown in Table 1, and the specific surface area is 14.92 m 2 / g.

[0085] Catalyst 3 Reviews:

[0086] Reaction 3: Weigh 2.5g of catalyst and add it to 100g of 30wt% maleic acid aqueous solution. After replacing the air with N2 five times, introduce hydrogen to replace N2 three times, and finally fill in 1.5MPa H2. Turn on the stirring to mix thoroughly, and then carry out hydrogenation reaction at 100℃. After reacting for 4h, stop heating and the reaction is over. When the kettle temperature drops to room temperature, take out the mixture in the kettle, place it in an oven and heat it to 60℃. After the solution is uniform, filter it while hot to obtain the catalyst, and place the filtrate at 5℃ for cooling and crystallization. The precipitated solid is succinic acid, and the remaining liquid is re-entered into the next cycle. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0087] Embodiment 4:

[0088] Catalyst 4 preparation:

[0089] (1) Add 2 mol of titanium oxynitrate and 0.008 mol of La(NO)3·6H2O to 1 L of deionized water and stir to obtain liquid A; add 2 mol of hexamethylenetetramine and 1.5 g of polyacrylamide (molecular weight 12 million) to 0.5 L of deionized water and stir to obtain liquid B; slowly add liquid A dropwise to liquid B for reaction at a reaction temperature of 75°C and a reaction end point pH of 1.5. The reaction is terminated after 6 hours of reaction.

[0090] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 h. 5 g of the dried precursor was taken and heated to 600°C under the condition of continuous N2 flow at 400 mL / min, and steam was introduced for 4 h, wherein the water vapor volume space velocity was 2 h -1 The number of surface hydroxyl groups per unit area of ​​the sample after water vapor treatment was measured, and the results are shown in Table 1.

[0091] (3) The metal active component Ru was loaded by the over-impregnation method. First, 40 mg of ruthenium chloride solution (Ru concentration was 20 wt%) was added to 20 mL of deionized water, mixed evenly, and then 4 g of the carrier was poured into it. After stirring at room temperature for 4 h, the filter cake was dried at 100 ° C for 8 h, and calcined at 700 ° C for 3 h to obtain the catalyst. The active component Ru loading amount was 0.2 wt% based on TiO2.

[0092] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain catalyst 4.

[0093] The particle size analysis of the carrier is shown in Table 1, and the average particle size is 13.2 μm. The BET fitting results of catalyst 2 are shown in Table 1, and the specific surface area is 34.92 m 2 / g.

[0094] Catalyst 4 Reviews:

[0095] Reaction 4: Weigh 1g of catalyst and add it to 100g of 10wt% citric acid aqueous solution. After replacing the air with N2 five times, introduce hydrogen to replace N2 three times, and finally fill in 4MPa H2. Turn on the stirring to mix thoroughly, and then carry out hydrogenation reaction at 60°C. After reacting for 6h, stop heating and the reaction is over. When the kettle temperature drops to room temperature, take out the mixture in the kettle, place it in an oven and heat it to 60°C. After the solution is uniform, filter it while hot to obtain the catalyst, and place the filtrate at 5°C for cooling and crystallization. The precipitated solid is succinic acid, and the remaining liquid is re-entered into the next cycle. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0096] Comparative Example 1

[0097] A catalyst with CeO2 as the carrier was prepared to investigate the stability of other supported catalysts in this system.

[0098] (1), (2) Compared with Example 2, cerium nitrate was used instead of titanium oxynitrate to prepare a CeO2 carrier doped with auxiliary Ni, wherein the doping amount of auxiliary Ni was 0.7%.

[0099] (3) The metal active component Ir is loaded by the over-impregnation method, and the specific method is the same as that in Example 2. The loading amount of the active component Ir is 0.5 wt % calculated as CeO2.

[0100] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 450°C for 120 minutes to obtain catalyst 5.

[0101] Catalyst 5 Reviews:

[0102] Reaction 5: The catalyst evaluation method is the same as in Example 2. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2. The XRD spectrum of the catalyst after eight cycles is shown in Figure 3 As shown in the figure, compared with the catalyst before the reaction, the crystalline structure of CeO2 is destroyed. This result shows that CeO2 does not have long-term stability in this system.

[0103] Comparative Example 2

[0104] Compared with Example 1, the support was not subjected to water vapor treatment.

[0105] Catalyst 6 Preparation:

[0106] (1) Same as Example 1.

[0107] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 hours, transferred to a muffle furnace and calcined at 500°C for 2 hours, and taken out after cooling to obtain a carrier. The surface hydroxyl number per unit area of ​​the carrier obtained after calcination was analyzed, and the results are shown in Table 1.

[0108] (3) The metal active component Pd is loaded by the over-impregnation method. The specific method is the same as that in Example 1, and the loading amount of the active component Pd is 0.2 wt% based on TiO2.

[0109] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain Catalyst 6.

[0110] The carrier was subjected to particle size analysis and catalyst 6 was subjected to BET fitting. The results are shown in Table 1.

[0111] Catalyst 6 Reviews:

[0112] The evaluation conditions were the same as those in Example 1. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0113] Comparative Example 3

[0114] Compared with Example 1, the uniform precipitation method is not used in the carrier preparation process, but a chemical precipitation method is used, in which ammonia water is used as a precipitant.

[0115] Preparation of Catalyst 7:

[0116] (1) Add 2 mol of titanyl sulfate and 0.005 mol of La(NO)3·6H2O to 1 L of deionized water and stir to obtain liquid A; add 2 mol of ammonia water and 1 g of dodecylbenzenesulfonic acid to 0.5 L of deionized water and stir to obtain liquid B; add 20 mL of bottom water to the reaction container, and react liquid A and liquid B in parallel at a reaction temperature of 90°C and a reaction pH of 7. The reaction is terminated after 4 hours.

[0117] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100° C. for 8 h. The dried material was treated with water vapor in the same manner as in Example 1. The number of surface hydroxyl groups per unit area of ​​the carrier after water vapor treatment was analyzed, and the results are shown in Table 1.

[0118] (3) The metal active component Pd is loaded by the over-impregnation method, and the specific method is the same as that in Example 1. The loading amount of the active component Pd is 0.2 wt% based on TiO2.

[0119] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain catalyst 7.

[0120] The particle size analysis of the carrier is shown in Table 1. Using ammonia water as a precipitant, the average particle size of the final prepared sample can reach 125 μm, and the particle size distribution diagram is shown in Figure 5 The BET fitting results of catalyst 7 are shown in Table 1.

[0121] Catalyst 7 Reviews:

[0122] Reaction 7: The evaluation conditions were the same as those in Example 1. The conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0123] Comparative Example 4

[0124] Compared with Example 4, the auxiliary agent is loaded after the carrier is prepared.

[0125] Catalyst 8 preparation:

[0126] (1) Add 2 mol of titanium oxynitrate to 1 L of deionized water and stir to obtain liquid A; add 2 mol of hexamethylenetetramine and 1.5 g of polyacrylamide (molecular weight 12 million) to 0.5 L of deionized water and stir to obtain liquid B; slowly add liquid A dropwise to liquid B for reaction, the reaction temperature is 75°C, the reaction end point pH is 1.5, and the reaction is terminated after 6 hours of reaction.

[0127] (2) The slurry prepared in step (1) is filtered, washed, dried, and treated with steam. The specific method is the same as that in Example 4.

[0128] (3) The metal active component Ru and the auxiliary component La were loaded by the over-impregnation method. First, 40 mg of ruthenium chloride solution (Ru concentration is 20 wt%) and 65.5 mg of La(NO)3·6H2O were added to 20 mL of deionized water, mixed evenly, and 4 g of the carrier was poured into it. After stirring at room temperature for 4 h, the filter cake was placed at 100 ° C for 8 h and calcined at 700 ° C for 3 h to obtain the catalyst. The active component Ru loading amount is 0.2 wt% based on TiO2, and the auxiliary component La accounts for 0.816 wt% of the mass of TiO2 based on oxide.

[0129] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain catalyst 8.

[0130] The particle size analysis of the carrier was performed and the BET fitting of the catalyst was performed. The results are shown in Table 1.

[0131] Catalyst 8 Reviews:

[0132] Reaction 8: Same as Example 4, the conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0133] Comparative Example 5

[0134] Compared with Example 1, the water vapor treatment temperature is increased.

[0135] Catalyst 9 preparation:

[0136] (1) Same as Example 1.

[0137] (2) The slurry prepared in step (1) was filtered, washed, and dried in an oven at 100°C for 8 h. 5 g of the dried precursor was taken and heated to 950°C under the condition of continuous N2 flow at 200 mL / min, and steam was introduced for 2 h, wherein the water vapor volume space velocity was 2 h -1 The number of surface hydroxyl groups of the carrier after water vapor treatment was measured, and the results are shown in Table 1.

[0138] (3) The active component impregnation conditions are the same as those in Example 1.

[0139] (4) The material prepared in step (3) was placed in an atmosphere furnace for reduction, using 5% H2 / Ar as a carrier gas, and reduced at 500°C for 60 minutes to obtain catalyst 9.

[0140] The particle size analysis of the carrier was performed, and the results are shown in Table 1. The XRD analysis of catalyst 9 was performed, and the results are shown in Table 1. Figure 5 As shown in the figure, it can be seen that the prepared catalyst 9 is in rutile phase.

[0141] Catalyst 9 Reviews:

[0142] Reaction 9: Same as Example 1, the conversion rate of maleic acid and the yield of succinic acid during the cycle are shown in Table 2.

[0143] Table 1 Analysis of properties of different catalysts

[0144]

[0145] Among them, D 50 (μm) represents the median particle size, that is, the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%.

[0146] Table 2 Reaction performance of catalysts in cycle experiments

[0147]

[0148] The specific embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical features of the present invention can be combined in any other suitable manner, and these simple variations and combinations should also be regarded as the scope disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for preparing succinic acid by aqueous phase hydrogenation of maleic acid, characterized in that: The catalyst comprises a carrier and an active metal. The carrier is a titanium dioxide carrier containing an additive. The additive is selected from at least one of La, Ga, Re, Mo, In, Ni and Mn, and is preferably at least one of La, Ga and Ni.

2. The catalyst according to claim 1, characterized in that: The carrier is a titanium dioxide carrier containing an additive, and the additive, calculated as oxide, accounts for 0.01% to 1.0% of the mass of TiO2 in the carrier, preferably 0.2% to 1.0%.

3. The catalyst according to claim 1, characterized in that: The number of surface hydroxyl groups per unit area of ​​the carrier is 5 to 15 (×10 mmol / m 2 ).

4. The catalyst according to claim 1, characterized in that: The active metal is selected from at least one of Pd, Pt, Ru, Rh and Ir; the content of the active metal accounts for 0.1wt% to 2.0wt% of the mass of TiO2 in the carrier.

5. The catalyst according to claim 1, characterized in that: The specific surface area of ​​the catalyst is 10 to 40 m 2 / g.

6. A method for preparing a catalyst according to any one of claims 1 to 5, characterized in that: include: (1) a solution A containing titanium and an additive reacts with an aqueous solution B containing a precipitant and a surfactant; (2) filtering, washing, drying, and steam-treating the slurry obtained in step (1) to obtain a carrier; (3) impregnating the support obtained in step (2) with a solution containing active metal components, and drying and calcining the impregnated material; (4) reducing the material prepared in step (3) to obtain the catalyst.

7. The method according to claim 6, characterized in that: In step (1), in the solution A containing titanium and additives, the titanium source is a soluble titanium salt, and the additive source is a soluble additive metal salt; the soluble titanium salt is preferably at least one of titanium oxysulfate and titanium oxynitrate; the soluble additive metal salt can be at least one of nitrate, sulfate, and chloride.

8. The method according to claim 6 or 7, characterized in that: In step (1), in the solution A containing titanium and additives, the concentration of Ti is 1.5 to 2.5 mol / L, and / or the amount of the additive added in terms of oxide is 0.01% to 1.0%, preferably 0.2% to 1.0%, of the mass of the titanium source in terms of TiO2.

9. The method according to claim 6, characterized in that: In step (1), in the aqueous solution B containing a precipitant and a surfactant, the precipitant is at least one of urea and hexamethylenetetramine, and the surfactant is at least one of dodecylbenzenesulfonic acid, anionic polyacrylamide, and polyethylene glycol; And / or, in step (1), in the aqueous solution B containing the precipitant and the surfactant, the concentration of the precipitant is 2 mol / L to 4 mol / L; And / or, in step (1), the amount of surfactant added is 0.5wt% to 3.0wt% of the mass of titanium in solution A calculated as TiO2.

10. The method according to claim 6, characterized in that: In step (1), the reaction mode of liquid A and liquid B is forward addition or reverse addition; wherein the reaction temperature is 75° C. to 95° C., the reaction time is 2 h to 6 h, and the pH value at the reaction endpoint is 1.0 to 3.

0.

11. The method according to claim 6, characterized in that: In step (1), the reaction mode of liquid A and liquid B is parallel flow; wherein the reaction temperature is 75° C. to 95° C., the reaction time is 2 h to 6 h, and the reaction pH value is 1.0 to 3.

0.

12. The method according to claim 6, characterized in that: In step (2), the drying conditions are as follows: drying temperature is 50°C to 100°C, and drying time is 2h to 14h.

13. The method according to claim 6, characterized in that: In step (2), the steam treatment is a continuous flow steam treatment, and the temperature is raised to the steam treatment temperature. The dry solid is in an inert gas atmosphere. The steam treatment conditions are as follows: the steam treatment temperature is 450°C to 700°C, the treatment time is 2h to 6h, and the steam feed volume space velocity is 0.05 to 2.0h -1 .

14. The method according to claim 6, characterized in that: In step (3), the drying conditions are as follows: drying temperature is 80°C to 120°C, and drying time is 2h to 14h; And / or, in step (3), the calcination conditions are as follows: the calcination temperature is 450°C to 700°C, and the calcination time is 2h to 4h.

15. The method according to claim 6, characterized in that: In step (4), the reduction is carried out in a hydrogen-containing atmosphere. Preferably, the reducing gas is a mixture of hydrogen and inert gas, wherein hydrogen accounts for 5% to 20% of the volume of the mixture. The reducing conditions are as follows: the reduction temperature is 500° C. to 650° C., and the reduction time is 30 min to 120 min.

16. Use of the catalyst according to any one of claims 1 to 5 or the catalyst prepared by the method according to any one of claims 6 to 15 in the preparation of succinic acid by aqueous phase hydrogenation of maleic acid.

17. The use according to claim 16, characterized in that: The application comprises: in the presence of hydrogen, an aqueous solution of maleic acid is contacted with the catalyst to react to obtain a product; The concentration of the maleic acid aqueous solution is 5wt% to 30wt%; The amount of the catalyst is 0.5wt% to 5wt% of the total mass of the maleic acid aqueous solution; The reaction conditions are as follows: hydrogen pressure is 0.7 MPa to 4 MPa, reaction temperature is 60° C. to 120° C., and reaction time is 1 h to 6 h.

Citation Information

Patent Citations

  • Method for preparing butanedioic acid under catalytic hydrogenation

    CN101844976B

  • Catalytic agent for synthesizing succinic acid through maleic acid hydrogenation and preparation method thereof

    CN102430404A

  • Preparation method of nitrogen doped carbon material protection acid-resistant hydrogenation catalyst and catalyst prepared through same

    CN103191767B

  • Catalyst for maleic anhydride aqueous phase hydrogenation direct synthesis of succinic acid, and preparation method and application thereof

    CN106861702A

  • Green production method of butanedioic acid

    CN107473954A